2011
DOI: 10.5511/plantbiotechnology.11.0428a
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of estragole by the plant cultured cells of Caragana chamlagu

Abstract: Estragole (EG) is biosynthesized in herbs including anise, basil, bay, tarragon, fennel and marjoram, and is thought to be a useful biomass for the food and health industries. Moreover, the metabolites from estragole are useful intermediates in organic synthetic chemistry. However, estragole has been transformed only by chemical methods, and no biocatalysts have been reported. In this paper, we report the biotransformation of estragole using the plant cells of Caragana chamlagu gave 4-methoxycinnamaldehyde (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…This work stems from other studies, which have demonstrated that certain soil bacteria are able to utilize eugenol 5 and isoeugenol 18 as food sources. The biotransformations processes illustrated in Scheme were proposed to occur via a radical pathway. It is thus possible to envisage that future processes will utilize biomass engineered to produce valuable phenylpropenes; these will include bioprocesses in which large amounts of allylpropenoid compounds could be isomerized in vivo into their isomerized derivatives (for example, the large-scale conversion of estragole 7 into anethole 20 ).…”
Section: Biochemical Isomerization Of Allylbenzenesmentioning
confidence: 99%
“…This work stems from other studies, which have demonstrated that certain soil bacteria are able to utilize eugenol 5 and isoeugenol 18 as food sources. The biotransformations processes illustrated in Scheme were proposed to occur via a radical pathway. It is thus possible to envisage that future processes will utilize biomass engineered to produce valuable phenylpropenes; these will include bioprocesses in which large amounts of allylpropenoid compounds could be isomerized in vivo into their isomerized derivatives (for example, the large-scale conversion of estragole 7 into anethole 20 ).…”
Section: Biochemical Isomerization Of Allylbenzenesmentioning
confidence: 99%